(untitled) (LAPAI JOURNAL OF NIGERIA HISTORY, 2023)
The recent fall in the oil price and subsequent drop in the federal subventions or grants to the states in Nigeria has propelled the intense study of revenue mobilization at the local government for rural development. It’s in light of this renewal effort towards research on rural development in the local government that this, research focuses basically on the search for an alternative to federal grants by the local authority thereby identifying effective revenue mobilization as the engine room for rural development. This survey research adopts both primary and secondary research instruments in the collection of data and uses statistical analogy in the interpretation of the data collected. The research argues among other things that, the deplorable condition of the rural areas is directly a function of less effective revenue mobilization and application by the local authority and thereby concludes that unless there is a renewal effective effort towards revenue mobilization the rural development will remain unrealistic and the research further finds among other things that local authority lack the political intensity to mobilized revenue and finally recommend among other thing that resources realized in the mobilization process should be channel to human development projects.